Approaches in the Indonesian Maritime identity Construction - Briliantina Putri (Journal Of Global Strategic Studies, 2023)
As the largest archipelagic country in Southeast Asia, Indonesia is by nature surrounded by the seas and strategically situated between the Indian and Pacific Oceans. Given this geographical circumstance, the Indonesian government claims that the country can be identified as a maritime nation. This article elaborates maritime identity construction in Indonesia by looking into constructed historical narratives of the country’s past maritime glory, and the policies taken by the Indonesian presidents in the maritime sector. The former signified the bottom-up approach in maritime identity construction, while the latter represented the top-down approach, underlining the role of state in maritime identity construction. The article concludes that Indonesia's maritime identity has evolved through different presidential eras, with President Joko Widodo's Global Maritime Fulcrum (GMF) vision marking an important milestone. The GMF not only influenced government priorities in national maritime sector but also shaped Indonesian government's perception of an increased global role in maritime affairs.